(3GdWhGdY GdefjQI Ydi YejQIs ((3efUhQ Hf Sdje Hf MSf Hf Ydi GdOejGWi GdCRgQi s)
(3ChdgG (B:s
(3hCbHdJ Ydi ESYGage HeWdhHge deG jhVM GdcJGH ZGjI GdEjVGM hjZfi Yf GdTQhM hGdMhGTi s
(3BNQgG (B:s
(3hYf GdQGHY Cfg CJi HVejQ GdeDfK HJChjd GdeQJHI hGdYXeI hGddg JYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs